THE ENVIRONMENTAL POLLUTION FROM MINING ACTIVITIES IN KIRKI, ALEXANDROUPOLIS AREA - Αρίκας, Κ.; Watzl, V.; Goetz, D. (Bulletin of the Geological Society of Greece, 2004)
Mining activities in Kirki ore deposit took place for a short period, from 1975 to1980 and 1990 to 1995. However, the waste piles and the remaining material of the floatation plant have become a significant source of large amount of toxic metals dispersed in the surrounding area. The dangerous wastes contain large amount of unexploited metal-concentrate and toxic chemicals from the former floatation plant (also a number of containers with unused sodium cyanide). All this toxic material is continuously transferred by the rainwater to the river Erini. This river discharges into Aegean sea at a distance of 23 km, on the east coast of Alexandroupolis town. The concentration level of the toxic metals such as Pb, Cu, Zn, As and Cd in the sediments of the river bed is 1140, 50, 290, 100 and 690 times over the stipulated standards.